Lessons from Yeast on Emerging Roles of the ATAD2 Protein Family in Gene Regulation and Genome Organization - Cattaneo, Matteo (Mol Cells, 2014)
ATAD2, a remarkably conserved, yet poorly characterized factor is found upregulated and associated with poor prognosis in a variety of independent cancers in human. Studies conducted on the yeast Saccharomyces cerevisiae ATAD2 homologue, Yta7, are now indicating that the members of this family may primarily be regulators of chromatin dynamics and that their action on gene expression could only be one facet of their general activity. In this review, we present an overview of the literature on Yta7 and discuss the possibility of translating these findings into other organisms to further define the involvement of ATAD2 and other members of its family in regulating chromatin structure and function both in normal and pathological situations.